2019
DOI: 10.1016/j.envpol.2019.113333
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological effects of As (V) in juvenile rockfish Sebastes schlegelii by a combined metabolomic and proteomic approach

Abstract: Arsenic (As) is a metalloid element that is ubiquitous in the marine environment and its contamination has received worldwide attention due to its potential toxicity. Arsenic can induce multiple adverse effects, such as lipid metabolism disorder, immune system dysfunction, oxidative stress and carcinogenesis, in animals. Inorganic arsenic includes two chemical forms, arsenite (As (III)) and arsenate (As (V)), in natural environment. As (V) is the dominant form in natural waters. In the present study, metabolom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 72 publications
2
6
0
Order By: Relevance
“…Cytoskeletal injuries in bivalves induced by metal pollution have been repeatedly confirmed (Gomes et al, 2013;Xu et al, 2016). And these cytoskeletal-related DEPs are generally contain actins, tubulins, and myosins in marine bivalves (Xu et al, 2019), a finding consist with our study's results. Consequently, the significantly altered cytoskeletal proteins demonstrate that oxidative stress and subsequent disturbed cytoskeleton and cell structures can be induced by Cd in deepsea mussels.…”
Section: Cytoskeleton Changes Associated With CD Exposuresupporting
confidence: 87%
See 2 more Smart Citations
“…Cytoskeletal injuries in bivalves induced by metal pollution have been repeatedly confirmed (Gomes et al, 2013;Xu et al, 2016). And these cytoskeletal-related DEPs are generally contain actins, tubulins, and myosins in marine bivalves (Xu et al, 2019), a finding consist with our study's results. Consequently, the significantly altered cytoskeletal proteins demonstrate that oxidative stress and subsequent disturbed cytoskeleton and cell structures can be induced by Cd in deepsea mussels.…”
Section: Cytoskeleton Changes Associated With CD Exposuresupporting
confidence: 87%
“…In the high-dose group, however, we found that NDUFA5 was unaltered, but all the proteins associated with oxidative phosphorylation (mitochondrial ATP synthase subunit d precursor and V-type proton ATPase 16 kDa proteolipid subunit) were up-regulated and related to ATP synthase, implying an increased demand for ATP production in deep-sea mussels. Increased oxidative phosphorylation was reported in the rock fish Sebastes schlegelii under arsenic exposure and the mussel Mytilus galloprovincialis under nano-Ag exposure, both revealing a process of energetic re-adjustment to counteract the effects of arsenic toxicity (Gomes et al, 2013;Xu et al, 2019). In particular, to compensate for the diminished energy supply caused by the inhibition of glycolysis and the TCA, deep-sea mussels bolstered amino acid levels in their body to protect themselves from more damage caused by high-dose Cd exposure (Table 2).…”
Section: Alteration Of Energy Metabolism Associated With CD Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomic studies can be performed using different analytical techniques, such as mass spectrometry (MS) (Courant et al, 2014) and nuclear magnetic resonance spectroscopy (NMR) (Watanabe et al, 2015). Proton nuclear magnetic resonance ( 1 H-NMR) spectroscopybased metabolomics is a commonly used tool for studying the effects of pollutants on the metabolic profiles of aquatic organisms, in laboratory or field-scale conditions (Cappello et al, 2017(Cappello et al, , 2016(Cappello et al, , 2013Jones et al, 2008;Kwon et al, 2012;Maisano et al, 2017;Tuffnail et al, 2009;Xu et al, 2019). Because the spectral peak areas are quantitatively related to metabolite concentrations, this technique simultaneously provides unbiased and reproducible data about a wide range of metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of metal pollutants on marine organisms can be studied by combining metabolomics and proteomics. As (V) not only affects metabolism and signal transduction of juvenile rockfish Sebastes schlegelii ., but also affects its cytoskeleton structure (Xu et al, 2019).…”
Section: Application Of Molecular Biology Methods In Pollution Controlmentioning
confidence: 99%